2017
DOI: 10.3928/01477447-20170418-04
|View full text |Cite
|
Sign up to set email alerts
|

Root Cause Analysis and Actions for the Prevention of Medical Errors: Quality Improvement and Resident Education

Abstract: The quality of care delivered by orthopedic surgeons continues to grow in importance. Multiple orthopedic programs, organizations, and committees have been created to measure the quality of surgical care and reduce the incidence of medical adverse events. Structured root cause analysis and actions (RCA2) has become an area of interest. If performed thoroughly, RCA2 has been shown to reduce surgical errors across many subspecialties. The Accreditation Council for Graduate Medical Education has a new mandate for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 15 publications
0
21
0
Order By: Relevance
“…[ 10 11 12 ] Root cause analysis is a management technique that has been utilized in various studies to understand the depth of the problem. [ 13 14 15 ] Similarly in this root cause analysis, we were able to delineate such factors that require attention and need a focused approach for solutions for an efficient, affordable primary health care practice.…”
Section: Discussionmentioning
confidence: 93%
“…[ 10 11 12 ] Root cause analysis is a management technique that has been utilized in various studies to understand the depth of the problem. [ 13 14 15 ] Similarly in this root cause analysis, we were able to delineate such factors that require attention and need a focused approach for solutions for an efficient, affordable primary health care practice.…”
Section: Discussionmentioning
confidence: 93%
“…The RCA squared process is one way to identify patient safety issues and develop meaningful systems-based improvement initiatives. 1,5 The perioperative skin assessment project implemented by staff members at JMH demonstrated that the return on investment for prevention is worth the effort.…”
Section: Resultsmentioning
confidence: 99%
“…2 The RCA squared process is used to identify system vulnerabilities and causal factors in an event and determine stronger actions to effectively reduce risk. 1,2 Using the RCA squared process, team members at John Muir Health (JMH) in Concord, California, were able to effectively develop and implement a nurse-driven quality improvement project focused on perioperative pressure injuries and cost-neutral strategies for prevention.…”
Section: Root Cause Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…33,34 The initial flow diagram ( Figure 2) is produced to show the chain of events preceding the incident. 35 Trigger questions are used to identify areas of inquiry that may otherwise be overlooked. 36,37 Individuals working in areas identified and outlined on the flow diagram are interviewed to elucidate specifics related to the surroundings, events that transpired, and the potential ''why.''…”
Section: Performing Rcamentioning
confidence: 99%